CLIL Methodology through Biography: Exploring Biography as a Tool for Language and Literature Learning (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Biography belongs to the essayistic category, and its generic and rhetorical components offer multiple possibilities for language teaching. One of its requirements is completeness. This implies the definition of a situational context, and an existential and spiritual universe for each character. The biographical subject must be formed from all the components of the person. These also include death. This methodological proposal considers all these concerns, with the purpose of taking them as learning tools. Specifically the recognition of a third historical person and its literary construction its location in time and space the description of its environment its morphology and personality its ideas and the alterities with which it interacts. The biographical discourse requires diegetic format for the account of life reflective discourse and introduction of the first person, both in the subjectivity and presence of the author and the reader. The historical basis provides an anchorage in the unavoidable reality for the Biography. However, since it is a literary genre, it allows the 'pact of fictionality'. This work proposes Biography, as a method for learning language and literature, through the cultural and existential contextcontents which it entails. Specially, because ‘biography’ is a different concept, according to culture and theodices.